Association between serum TSH levels and metabolic components in euthyroid subjects: a nationwide population-based study - Ren R (Dove Medical Press, 2019)
Rui Ren,1,2 Yu Ma,2 Fang Deng,1 Tao Li,1 Hongyan Wang,2 Jing Wei,3 Xiaoyan Jiang,2 Min He,1 Mingyuan Tian,4 Dongfang Liu,4 Bing Chen,1 Wuquan Deng1,21Department of Endocrinology and Nephrology, Chongqing University Central Hospital, Chongqing Emergency Medical Center, Chongqing, People’s Republic of China; 2Department of Endocrinology, Southwest Hospital, Army Medical University, Chongqing, People’s Republic of China; 3Department of Endocrinology, General Hospital of Xinjiang Military Region, PLA, Urumqi, People’s Republic of China; 4Department of Endocrinology, The Second Affiliated Hospital, Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Wuquan DengDepartment of Endocrinology and Nephrology, Chongqing University Central Hospital, Chongqing Emergency Medical Center, No. 1 Jiankang Road, Yuzhong District, Chongqing, People’s Republic of ChinaTel +86 236 369 2185Email wuquandeng@gmail.comBackground: Whether a relationship exists between various metabolic factors and thyroid-stimulating hormone (TSH) levels in euthyroid persons remains unknown. This study aims to explore the relationship between TSH levels and metabolic factors in euthyroid individuals.Methods: A total of 2,663 subjects were enrolled from a nationwide population-based cross-sectional survey of iodine nutrition, thyroid disease and diabetes in China (2014–2017). Euthyroid individuals were divided into four groups according to quartiles of TSH levels: group A (n=305, 0.3–1.3 mIU/L), group B (n=829, 1.3–2.2 mIU/L), group C (n=673, 2.2–3.2 mIU/L) and group D (n=349, 3.2–4.2 mIU/L). Anthropometric parameters, biochemical indicators and TSH levels were determined.Results: A total of 2,156 euthyroid subjects with serum TSH levels within the normal range accounted for 86.8% of the sample. The systolic blood pressure (SBP) in group D was significantly higher than that in the other three groups. Group C displayed significantly lower thyroid peroxidase antibody (TPOAb) levels than the other three groups. Group C also had lower anti-thyroglobulin antibody (TgAb) levels than groups A and D, whereas the TgAb levels in group B were only lower than those in group A. Spearman’s or Pearson’s linear regression analysis showed that SBP (r=0.054; P=0.013) was positively correlated with TSH, but cholesterol (TC) (r=−0.043, P=0.047) was negatively correlated with TSH. Multiple stepwise regression analysis revealed that SBP, the urinary iodine concentration (UIC), waist circumference (WC), body mass index (BMI), TC, triglycerides (TGs) and low-density lipoprotein cholesterol (LDL-C) were independent predictors of serum TSH levels.Conclusion: This large population-based study demonstrates a significant interaction between metabolic factors and TSH levels. An adverse weight status, high blood pressure levels, blood lipid metabolism disorder and excessive iodine intake may be early manifestations of thyroid disease in euthyroid subjects.Keywords: thyroid-stimulating hormone, metabolic syndrome, iodine nutrition, euthyroid state